Late‐life personality traits, cognitive impairment, and mortality in a population‐based cohort. (14th May 2020) - Neuvonen, Elisa; Hall, Anette; Tolppanen, Anna‐Maija; Ngandu, Tiia; Rusanen, Minna; Laatikainen, Tiina; Soininen, Hilkka; Kivipelto, Miia; Solomon, Alina
Abstract: Objectives: We examined longitudinal associations between late‐life personality traits and cognitive impairment, dementia, and mortality in the population‐based Cardiovascular Risk Factors, Aging and Dementia (CAIDE) Study. Methods: Anger expression and trait anger (State‐Trait Anger Expression Inventory), anxiety (State‐Trait Anxiety Inventory), and sense of coherence (Sense of Coherence Scale) were assessed at the 1998 CAIDE visit (1266 cognitively normal individuals, mean age 71.0 years). Totally, 582 participants had complete re‐examination in 2005‐2008 (105 mild cognitive impairment, MCI; and 29 dementia). National registers data until 2008 were also used for both participants and nonparticipants to ascertain incident dementia (96 cases) and mortality (227 died). Analyses were adjusted for age, sex, education, follow‐up time, cardiovascular and lifestyle factors, and depressive symptoms. Results: Higher anxiety was associated with higher risk of MCI/dementia (OR 1.68, 95% CI 1.07‐2.63) and death (HR 1.46, 95% CI 1.08‐1.98). High sense of coherence was associated with lower mortality (HR 0.65, 95% CI 0.45‐0.93). These associations were attenuated after accounting for depressive symptoms (OR 1.57, 95% CI 0.96‐2.58 for anxiety‐MCI/dementia; HR 1.35, 95% CI 0.97‐1.86 for anxiety‐mortality; and HR 0.68, 95% CI 0.45‐1.04 for sense of coherence‐mortality). Trait anger was associated with higher dementia risk even after adjustments (HR 1.90, 95% CI 1.14‐3.18). Conclusions: Anxiety was linked to worse cognitive outcome and mortality and sense of coherence to lower mortality. Depressive symptoms attenuated the associations. As a novel finding, trait anger was connected to dementia risk. These findings emphasize the importance of personality‐related risk factors for dementia and mortality. J Am Geriatr Soc 68:‐, 2020.